1992
DOI: 10.1259/0007-1285-65-773-361
|View full text |Cite
|
Sign up to set email alerts
|

High-intensity zone: a diagnostic sign of painful lumbar disc on magnetic resonance imaging

Abstract: The prevalence, validity and reliability of high-intensity zones in the annulus fibrosus seen on T2-weighted magnetic resonance images of patients with intractable low-back pain were determined. This sign was readily recognized by two independent observers. It occurred in 28% of 500 patients undergoing magnetic resonance imaging for back pain. The presence of a high-intensity zone correlated significantly with the presence of Grade 4 annular disruption and with reproduction of the patient's pain. Its sensitivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
312
4
11

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 583 publications
(334 citation statements)
references
References 34 publications
7
312
4
11
Order By: Relevance
“…Hypothetically, such leakage could be characterized by a region of high signal intensity in the otherwise low signal AF. One example of such high signal intensity in the IVD are High Intensity Zones (HIZ) which represents annular fissures [22]. Hypothetically, due to the common sub-voxel size of annulus fissures, only a minority of these fissures are fully visualized in MR images.…”
Section: Discussionmentioning
confidence: 99%
“…Hypothetically, such leakage could be characterized by a region of high signal intensity in the otherwise low signal AF. One example of such high signal intensity in the IVD are High Intensity Zones (HIZ) which represents annular fissures [22]. Hypothetically, due to the common sub-voxel size of annulus fissures, only a minority of these fissures are fully visualized in MR images.…”
Section: Discussionmentioning
confidence: 99%
“…The high signal contained within the annulus of a disc, separated from the nucleus pulposus, on lumbar spine MRI was termed as the HIZ by Aprill and Bogduk [1] in 1992. They correlated the finding with computed tomography discography and found that it had a positive predictive value of 86% for a severely disrupted, painful disc on awake discography.…”
Section: Discussionmentioning
confidence: 99%
“…According to the original study by Aprill and Bogduk [1], the HIZ was localized in midline within the posterior annulus (Fig. 1).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…High-intensity zone in the posterior annulus of the intervertebral disc on T2-weighted MR images High-intensity zones [2] in the posterior annulus of the intervertebral disc considered to reflect symptomatic intervertebral disc disorder were observed in 12 patients (30%). The zone was consistent with the enhanced region in the Gd-DTPA enhanced T1-weighted MR images in all patients.…”
Section: Mr Images Degree Of Disc Degeneration On T2-weighted Mr Imagesmentioning
confidence: 99%